Effects of Poultry Biochar on Electrochemical Properties of an Alfisol and Vertisol of Northern Nigeria - Victor Odiamehi Onokebhagbe; Kingsley Chinyere Uzoma; Lawal Mubarak; Auwalu Abubakar Kwalam; Habib Dahiru Wakili (CV. Literasi Indonesia, 2021)
This study was aimed to know the effects of biochar on charge properties of an Alfisol and Vertisol of semi-arid soils of Northern Nigeria. A laboratory experiment was conducted to determine the effects of biochar on point zero charge of soils. Experiment was laid out in a complete randomized design and consisted of two factors; 2 soil types and biochar at 4 levels giving a total of 8 treatment combinations with 3 replications each.The results obtained from the study showed that the pH in KCl of the incubated soils ranged from 7.3 to 7.4 and 7.6 to 7.9 for the Alfisol and Vertisol; 7.5 to 7.7 and 7.9 to 8.3 pH in H2O, was obtained for the Alfisol and Vertisol respectively. Electrical conductivity obtained ranged from 3.22 to 4.72 and 2.88 to 4.21 dS m-1 for Alfisol and Vertisol respectively. Electrical potentials ranged from -19.70 to -35 and -31.45 to -63.04 for the Alfisol and Vertisol respectively. The Point Zero Charge of soils correlated positively with the properties of the soils and the biochar rates.The addition of biochar to soils modified the PZC, increased the pH, electrical conductivity (ECe) and cation exchange capacity (CEC) of the soils.